The Agenda below the Radar. Disinformation and Fact-Checking on (Im)Migration - Magallon-Rosa, Raul (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The objective of this work is to analyze how rumors and hoaxes about immigration are used as a tool to disseminate a problem, the xenophobic discourse, which is beyond the reach of traditional media. However, this type of disinformation ends up affecting the perception that the media outlets transmits about this problem.The value of this research is in the combination of public data —the Spanish Centre for Sociological Research barometers— with the internal database of hoaxes and debunks that have been developed from the Maldita journalistic organization between 2017 and 2019. The evolution of the agenda on (in)migration is studied from a recent research point of view, not through its correspondence with the media outlets but through its convergence relationship with social networks and, specifically, with the new forms of disinformation.
Keywords: disinformation; immigration; fact-checking; hoaxes; Spain